BAHASA PERSUASIF GURU DALAM PEMBELAJARAN BAHASA INDONESIA SISWA KELAS VII SMP NEGERI 18 MAKASSAR: Teachers' Persuasive Language in Indonesian Language Learning for Grade VII Students at SMP Negeri 18 Makassar - Sarah; Sultan; Baharman (Journal of Applied Linguistics and Literature, 2026)
This study aims to describe the forms and functions of teachers’ persuasive language in Indonesian language teaching. The research method employed is qualitative descriptive. The results of the study indicate that the forms of teachers’ persuasive language in Indonesian language teaching include invitations, commands, assertions, questions, suggestions, and advice. The functions of teachers’ persuasive language in Indonesian language teaching include referential, expressive or emotive, appellative or conative, phatic, metalinguistic, and poetic. The use of persuasive language by teachers plays a vital role in creating effective interaction and encouraging active student participation in learning. In the Indonesian language learning process, teachers frequently use persuasive language to encourage, influence, and motivate students when they lack motivation to learn